1998
DOI: 10.1104/pp.117.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Expression of Three Cold-Induced Genes,blt101, blt4.9, and blt14, in Different Tissues of the Crown and Developing Leaves of Cold-Acclimated Cultivated Barley1

Abstract: Tissues expressing mRNAs of three cold-induced genes, blt101, blt14, and blt4.9, and a control gene, elongation factor 1␣, were identified in the crown and immature leaves of cultivated barley (Hordeum vulgare L. cv Igri). Hardiness and tissue damage were assessed. blt101 and blt4.9 mRNAs were not detected in control plants; blt14 was expressed in control plants but only in the inner layers of the crown cortex. blt101 was expressed in many tissues of cold-acclimated plants but most strongly in the vascular-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…In addition to SOS1, the promoter activity of a hypothetical osmosensor, ATHK1, seemed to be higher in vascular bundles, especially in the roots (Urao et al, 1999). Some stressinducible and tolerance genes/proteins, such as late-embryogenesis abundant (LEA) proteins and Ca 21 -dependent protein kinase, are also expressed very highly in the vascular area (Pearce et al, 1998;Saijo et al, 2001). Furthermore, one of the ABA-inducible genes, rab16A, is detected in vascular bundles and is induced in the leaves and roots by ABA, NaCl, and desiccation treatments .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SOS1, the promoter activity of a hypothetical osmosensor, ATHK1, seemed to be higher in vascular bundles, especially in the roots (Urao et al, 1999). Some stressinducible and tolerance genes/proteins, such as late-embryogenesis abundant (LEA) proteins and Ca 21 -dependent protein kinase, are also expressed very highly in the vascular area (Pearce et al, 1998;Saijo et al, 2001). Furthermore, one of the ABA-inducible genes, rab16A, is detected in vascular bundles and is induced in the leaves and roots by ABA, NaCl, and desiccation treatments .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to Folch and Lees (1951), ZmTLA1 represents a proteolipid, a class of extremely hydrophobic proteins. Only a few plant proteolipids are known (Capel et al, 1997;Pearce et al, 1998), and functions have not been identified for any of them. One proteolipid family highly conserved in eukaryotes (including plants) was predicted to contain two a-helical structures.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of coldinducible genes (RC12A, RC12B, COR6.6, COR15, COR78, DREB1, RD29A, and KIN1) during Arabidopsis development has been studied in detail, and the results indicated that the expression of these genes is regulated in different tissues both in stressed and unstressed conditions (Yamaguchi- Shinozaki and Shinozaki, 1993;Baker et al, 1994;Wang and Cutler, 1995;Xu et al, 1995;Medina et al, 2001). Lowtemperature-responsive genes (BLT101, BLT4.9, and BLT14) have been reported in barley, and these genes are also regulated during development (Pearce et al, 1998). It is possible that many genes regulated during plant development are also regulated by environmental stresses.…”
Section: Discussionmentioning
confidence: 99%